Factors affecting DH plants in vitro production from microspores of European radish - E. V. Kozar; E. A. Domblides; A. V. Soldatenko (Вавиловский журнал генетики и селекции)
Over the recent years the market demand for scaling up the production of European radish (Raphanus sativus L.) varieties and hybrids for open and protected production, varying in ripeness group, root shape and color, has drastically increased. Therefore, the expansion of genetic diversity and acceleration of the selection process are important. Doubled haploid technology considerably curtails the time required for creation of homozygous constant parental cell lines when in vitro microspore culture is used as the most promising method. For the first time, we were able to realize the full production cycle of DH plants of European radish by in vitro microspore culture up to inclusion of the produced material into the selection process. We have selected: preferable flower bud size, heat shock parameters, induction and regeneration media. It was revealed that linear length on the flower buds with the best possible stage of microspore development is genotype-specific: the flower bud length 2.8-3.3 mm is optimal for accessions of Rhodes and 3.7-4.2 mm is optimal for accessions of Teplichny Gribovsky. Heat shock at 32 °C for 48 hours is the most suitable for most genotypes. For the first time Murashige and Skoog based culture medium has been used for embryogenesis induction, and a major dependence of embryogenesis induction on the genotype x medium interaction was found. At regeneration and tiller stage it is advisable to add 1 mg/mL of benzylaminopurine and 0.1 mg/L of gibberellic acid to the medium, and rotting of micro-sprouts is performed with the use of hormone-free medium. Analysis of the produced regenerant plants by chromosome count and cell nucleus flow cytometry showed that 69 % of plants have a diploid chromosome set, 9 % have a haploid chromosome set, and 22 % have mixoploids and aneu-ploids chromosome sets. The seed progeny from doubled haploids and mixoploids were obtained by self-pollination, where all R1 plants had a doubled set of chromosomes. This study launches the development of an efficient method of radish doubled haploid production to be used in the selection process.